Novel 3-D resistor network simulation method for mixed ionic and electronic conducting electrodes - Setevich, Cristian F. (2024)
In this study, we propose and analyze a new resistor network model designed for the analysis of electrodes with mixed conductivity in solid oxide fuel cells (SOFCs). Resistor networks simulation for electrodes with mixed ionic and electronic conductivity oxides (MIEC) is not typically used due to the presence of oxygen ions and electrons as charge carriers. To address this complexity within the model, two resistor networks are employed. These networks conduct the different electrical species, and are linked through a resistor representing the charge transfer (CT) process. In the case of mixed-conducting electrodes, this CT occurs at the surface exposed to the gas phase. The electrode simulated in this study is generated using the discrete element method of random sphere insertion, and subsequently voxelized to create the resistor network. This method considers the geometric and microstructural parameters of the electrode, such as porosity, particle size, and electrode thickness. Electrical parameters are incorporated into the network through the values of the various conductivities characterizing MIEC oxides and including CT interface conductivities. By integrating geometric, microstructural, and electrical parameters, the model accurately captures the behavior of the electrodes. The close agreement between simulation and experimental/theoretical results highlights the efficacy of the approach in elucidating the electrochemical processes occurring at the MIEC electrode.